Pengaruh Variasi Lip Thickness pada Nozzle Terpancung terhadap Karakteristik Api Pembakaran Difusi Concentric Jet Flow - Faizal, Elka; Widodo, Agung Sugeng; Sasongko, Mega Nur (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2016)
Nozzle shape greatly influence turbulence between the fuel, air and formation of flow recirculation zone to produce a homogeneous mixing and get a near-perfect combustion. The recirculation zone is area that caused by flow rate breakdown, causing vortex and backflow around the end of nozzle. This backflow that hold up while lowering the flame so the flow rate of fuel and air mixture maintained lower or equal with flame speed. This study used variation of lip thickness of truncated nozzle 0, 4, 8, 12, and 16 mm.To obtain flame stability, fuel velocity and air velocity were variated. Thermocouples were used to measure flame temperature and its distribution. The results showed that stability of concentric jet diffusion flame flow increased with narrow lip thickness on a truncated nozzle. The wider stability area obtained in 4 mm lip thickness. In addition, temperature on diffusion flames concentric jet flow also more evenly distributed evenly with size of the nozzle lip thickness. The highest temperature and temperature distribution in the horizontal direction were occured in in the nozzle with lip thickness of 0 mm. A shadowgrapgh visualization was also used to identify phenomena of the nozzle exit flow.